The levelized cost of negative CO2 emissions from thermochemical conversion of biomass coupled with carbon capture and storage. (1st June 2021) - Cheng, Fangwei; Small, Arthur A.; Colosi, Lisa M.
Graphical abstract: Highlights: A decision framework is developed to evaluate the economic feasibility of negative emissions technologies. Climate change and economic performances of the 24 combinations of thermochemical conversion technologies, biomass, and reaction conditions are evaluated. Levelized cost of negative CO2 emission is computed for 24 cases. Virginia is estimated to have 11 million metric ton CO2 eq sequestration capacity at a total cost of 1.08 billion annually. Abstract: Negative emissions technologies (NETs) that remove and store CO2 from the atmosphere will play crucial roles in mitigating greenhouse gas emissions. Bioenergy with carbon capture and storage (BECCS) that combines biomass conversion for energy production and CO2 capture and storage is a NET that has been intensively studied to meet climate goals. This study evaluates the feasibility of four thermochemical conversion technologies (e.g., hydrothermal treatment, pyrolysis, gasification, and conventional combustion) of selected feedstocks (e.g., crop residues, woody wastes, and biosolid) coupled with carbon capture and storage as NETs. A combination of machine learning approaches, life cycle assessment (LCA), and economic analysis is used to assess the environmental and economic performances of pathways comprising different combinations of technologies, feedstock properties, and reaction conditions. Levelized cost of negative CO2 emissions (LCNC), which is defined as the carbon incentives that are required for a NET to break even, is computed for each pathway to provide a clearer picture of the economic feasibility and carbon mitigation potential of evaluated NETs. Our results show that slow pyrolysis of woody wastes and crop residues constitute economically viable NETs even without carbon incentives. Other pathways, on the other hand, require carbon incentives to make projects break even. A case study in Virginia reveals the carbon sequestration and economic burdens of evaluated NETs and suggests that woody wastes and crop residue combustion coupled with CCS could effectively contribute to most of the negative carbon sequestration in Virginia (98%). In contrast, hydrothermal treatment of biosolids and slow pyrolysis of crop residues have marginal contributions due to high LCNC and the small market size of products, respectively. Use of all available waste biomasses as feedstocks would correspond to 11 million metric ton CO2 eq sequestration and 1.09 billion economic burdens (without carbon credits) annually, with an average LCNC of 100/t CO2 eq in Virginia.